Harnessing Artificial Intelligence for Early and Evolution of Alzheimer’s Disease Detections and Enhancing Senior Mental Health through Innovative Art-Singing Therapies: A Multidisciplinary Approach - Jocelyne, Kiss; Geoffreyjen, Edwards; Rachel, Bouserhal; Elaine, Champagne; Thierry, Belleguic; Valéry, Psyché; Charles, Batcho; Carol, Hudon; Sylsvie, Ratté; Ingrid, Verdruyckt; Marie-Hélène, Parizeau; Liu-Rosenbaum, Aaron; et al. (Journal of Community Medicine and Health Solutions, 2023)
The well-documented therapeutic potential of group singing for patients living with Alzheimer’s disease (PLAD) has been hindered by COVID-19 restrictions, exacerbating loneliness and cognitive decline among seniors in residential and long-term care centers (CHSLDs). Addressing this challenge, the multidisciplinary study aims to develop a patient-oriented virtual reality (XR) interaction system facilitating group singing for mental health support during confinement and enhancing the understanding of the links between Alzheimer’s disease, social interaction, and singing. The researchers also propose to establish an early AD detection system using voice, facial, and non-invasive biometric measurements and validate the efficacy of selected intervention practices. The methodology involves co-designing an intelligent environment with caregivers to support PLAD mental health through online group singing, addressing existing constraints in CHSLDs. The researchers will engage volunteers in remote singing interactions and validate the impact of voice stimulation for PLADs using a control group. The primary expected outcome is the development of an “Intelligent Learning Health Environment,” fostering interactions while adapting to individual PLAD situations and incrementally accumulating knowledge on AD signs. This environment will facilitate the transfer of knowledge and technologies to promote non-verbal interactions via singing, enabling intervention at the first symptoms. Additionally, the research will contribute to transforming CHSLDs’ living environments, informed by neuroscience insights, and potentially extend the “collaborative self-care” approach to support seniors in aging safely and healthily at home.